An Overview on Etiology of Corneal Blindness - Kalaivani, K. (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
Aim: To screen for people with corneal blindness, to identify the etiology and to assess the risk factors for corneal blindness in Puducherry Union Territory. Materials and Methods: About Fifty patients with corneal opacity and with the visual acuity less than 6/60 clinically, aging between five years to eighty years were enrolled for this study. A detailed history regarding the etiology, nature of injury, pervious corneal disease or ocular surgery was recorded for each patient. External eye examination and slit lamp biomicroscopic examination to assess the size, site and depth of corneal opacity, presence of vascularization or ghost vessels and the anterior segment pathology was performed. Visual acuity was recorded using the Snellen’s chart and intra ocular pressure was measured with applanation tonometer. Results: Mean age of the study population was forty two years; Twenty seven patients were male and remaining twenty three were female; Seventeen people had bilateral involvement, nineteen had right eye and fourteen had only left eye involvement. Study population includes farmers, laborers, students, housewives, mason and others. Twenty one patients were found to have infective etiology; fourteen had injury, rest had postsurgical, nutritional and degenerative causes. Conclusion: Infective keratitis is the leading cause of corneal blindness in this study, trauma being the next cause. Occupation is an important risk factor. Health awareness and safety measures can help to reduce the incidence of corneal blindness.